마우스 모델에서 재생탕의 압박 손상 치료 효과 및 기전 연구 - 이지혜; Ji Hye Lee; 정민지; Min Ji Jung; 신미래; Mi-rae Shin; 안희연; Hui Yeon An; 배성은; Seong Eun Bae; 김민주; Min Ju Kim; et al. (大韓本草學會誌, 2025)
Objectives : This study aimed to investigate the wound-healing effects and underlying mechanisms of Jasaeng-tang (JT) in a murine model of pressure injury (PI) induced by ischemia/reperfusion (I/R). Specifically, the study focused on evaluating the therapeutic potential of JT in modulating oxidative stress, inflammation, and tissue remodeling processes associated with PI pathogenesis. Methods : A PI mouse model was established by inducing repeated cycles of I/R, followed by daily oral administration of JT 3.7 g/kg for 12 days. Serum levels of reactive oxygen species (ROS), malondialdehyde (MDA), and inflammatory cytokines were measured to evaluate oxidative stress and inflammatory responses. Western blotting was conducted to assess inflammation-related proteins, signaling proteins involved in physiological regulation, and apoptosis-related proteins. Histopathological changes were examined using Hematoxylin & Eosin (H&E) and Masson's Trichrome (M/T) staining. Results : JT significantly reduced the wound area and suppressed serum levels of ROS, MDA, tumor necrosis factor (TNF)-α, and interleukin (IL)-6. It also decreased the protein expression of inflammatory enzymes by inhibiting the activation of nuclear factor-kappa B (NF-κB) while significantly enhancing the expression of anti-inflammatory cytokines. Moreover, JT promoted cell survival by activating the phospho-phosphoinositide 3-kinase (p-PI3K)/ phospho-protein kinase B (p-Akt)/mammalian target of rapamycin (mTOR) signaling pathway and regulating apoptosis-related proteins. H&E and M/T staining results revealed that JT improved histological changes caused by PI. Conclusions : JT exhibits significant therapeutic potential in enhancing wound repair and mitigating PI progression through the suppression of ROS generation and regulation of inflammation-related signaling pathways.